A Contactless Palmprint Biometric System Based on CNN - Ebrahim A. M.Alrahawe,Vikas T. Humbe, G. N. Shinde (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Personal recognition systems have emerged as highly important in the information society. Biometric systems are widely used because its reliability in distinguishing between the subjects. Contactless biometric systems are more important because of their advantages, especially, during the pandemic of COVID19 as they can be used to avoid the spread of such viruses. Convolutional neural networks (ConvNet) have also gained a great success in large-scale image. In this study, we try to produce a contactless biometric system based on palmprint and use of Tungji large-scale contactless dataset to implement the system. This paper, divided into five sections, starts with the general introduction; a literature review of related work in the second section; the methodologies and dataset description the third section; the results and implementation steps in the fourth section; and finally, the conclusion and suggestions in the last section.